PROGRAM KOMUNIKASI PEMASARAN UNTUK MENINGKATKAN REVENUE FOOD & BEVERAGE 11/12 ROOFTOP BAR SEMARANG SEBAGAI ACCOUNT EXECUTIVE DAN PUBLIC RELATIONS - Agatha Christina Margaretha; Nurist Surayya Ulfa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The food and beverage (F&B) industry in Semarang is highly competitive, causingfluctuating revenue at 11/12 Rooftop Bar ARTOTEL Semarang that has not reached theexpected target. This study aims to design and implement an Integrated MarketingCommunication (IMC) program from October 2025 to January 2026 to increase Food &Beverages revenue through event marketing (Korokke Halloween Night, After Track, SunsetRooftop Yoga) and sales promotion (Buy 1 Get 1 Gin & Tonic, Promo KTM 10%). The resultsshow that this strategy successfully increased visitor numbers and transactions, resulting in arevenue increase of 7.26%, exceeding the target of 7.02%.